Pelatihan Pijat dan Lulur untuk Meningkatkan Skill Serta Pertumbuhan Ekonomi Warga Binaan Panti Sosial PGOT Mardi Utomo - Aulia Romadona; Kuswidyaningrum N.J (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Massage and Scrub Training to Improve Skills and Economic Growth for Residents of the PGOT Mardi Utomo Social Home. This training will begin with theory and practice. The theory refers to client diagnosis, followed by five basic movements and cost calculations. After receiving t Massage and Scrub Training to Improve Skills and Economic Growth for Residents of the PGOT Mardi Utomo Social Home. This training will begin with theory and practice. The theory refers to client diagnosis, followed by five basic movements and cost calculations. After receiving the training, inmates will also gain an understanding of spa and body scrub massage.The training's rationale is to respond to the needs of inmates and to assist with their individual needs. These massage and body scrub services are services for body care, such as relaxation.The training's rationale is to respond to the needs of inmates and to assist with their individual needs. These massage and body scrub services are services for body care, such as relaxation.he training, inmates will also gain an understanding of spa and body scrub massage. The training's rationale is to respond to the needs of inmates and to assist with their individual needs. These massage and body scrub services are services for body care, such as relaxation. The training's rationale is to respond to the needs of inmates and to assist with their individual needs. These massage and body scrub services are services for body care, such as relaxation. Ongoing activities, assisting partners in implementing activities and additions to the Tri Dharma of Higher Education